Biomechanical Comparison of Dynamic Hip Screw, Proximal Femoral Nail, Cannulated Screw, and Monoaxial External Fixation in the Treatment of Basicervical Femoral Neck Fractures - GÜRKAN, VOLKAN; IMREN, Y.; BİLSEL, İSMAIL KEREM; Gurkan, VOLKAN; TUNCAY, İBRAHİM; Bilsel, K.; DESTELI, E. E.; Tuna, M.; Gurcan, C.; Tuncay, I.; Sen, C. (My University, 2015)
PURPOSE OF THE STUDY